Thyroid Crisis and Septic Suspected Sepsis in the First Trimester of Pregnancy - Mahmudah Hidayati; Banundari Rachmawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
A normal pregnancy with physiological and hormonal changes can change thyroid function, accordingly, there are difficulties to establish the diagnosis of thyroid abnormality. The prevalence of hyperthyroidism in pregnancy is 0.6%. Approximately 1-2% of hyperthyroidism develops into a thyroid crisis. Knowledge of the diagnosis of the thyroid crisis in a pregnant female is very important to avoid complications. The 22-year-old female of thirteen weeks presented with vomiting, since two days before hospitalized, weakness, and decreased consciousness. During treatment, patients had diarrhea, melena, and was irritable. Physical examination showed blood pressure of 136/112 mmHg, pulse of 110 times/minute, respiration of 24 times/minute, and temperature of 38.3oC. Exophthalmos was found at the patient's eyes, but there was no enlargement of the thyroid and the patient often screamed hysterically. Routine urine examination showed proteinuria 1+, blood 3+, leukocytes 1+ in urinalysis, FT4 35.18 pmol/L and TSH <0.05 uIU/mL, leukocytes 15.2 x103/uL, SGOT 245 U/L, SGPT 366 U/L. The final diagnosis of this patient is a thyroid crisis and suspect sepsis in the first trimester of pregnancy. Thyroid Receptor Antibody (TRAb) examination should be performed to assure Graves disease or hyperthyroidism due to pregnancy (transient hyperthyroidism) as the cause.